Perceived effectiveness of cancer screening among family medicine and internal medicine physicians in the United States - Trishnee Bhurosy; Michelle T. Bover Manderski; Carolyn J. Heckman; Nishi J. Gonsalves; Cristine D. Delnevo; Michael B. Steinberg (Preventive Medicine Reports, 2022)
Family and internal medicine physicians play an important role in cancer screening, yet there are limited data on their beliefs regarding effectiveness of screening tests, which may affect physicians’ likelihood to recommend such tests. The study purpose was to assess current beliefs among family medicine and internal medicine physicians regarding effectiveness of various types of cancer screening. A national sample of 582 physicians from the American Medical Association’s Physician Masterfile were surveyed. Participants were asked about their perceived effectiveness of screening for colon, lung, breast, prostate, and cervical cancer among average, healthy individuals. Chi-square tests were conducted to assess relationships between perceiving screening tests to be ‘very effective in reducing cancer-related mortality’ and demographic characteristics. A substantial majority of physicians perceived colonoscopy (83.8%) and Pap smear (82.9%) to be very effective. Perceiving low-dose computed tomography (LDCT), Pap smear, and prostate-specific antigen (PSA) as ‘very effective’ differed by gender, with females less likely to endorse LDCT and Pap smear but more likely to endorse PSA. Perceiving PSA as ‘very effective’ differed by age and graduation year, with younger or more recently graduated physicians being less likely to perceive PSA as ‘very effective’. Non-Hispanic Black/African-American physicians were more likely to perceive mammography as ‘very effective’ than other groups. Physicians’ perceived effectiveness about cancer screening tests varies widely and may influence their recommendations or usage of these tests. Understanding physicians’ beliefs can help in improving uptake of evidence-based screening tests by providers and patients to promote early detection and successful treatment.